If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(-4x+13)=17x-7(2x-10)
We move all terms to the left:
-8(-4x+13)-(17x-7(2x-10))=0
We multiply parentheses
32x-(17x-7(2x-10))-104=0
We calculate terms in parentheses: -(17x-7(2x-10)), so:We get rid of parentheses
17x-7(2x-10)
We multiply parentheses
17x-14x+70
We add all the numbers together, and all the variables
3x+70
Back to the equation:
-(3x+70)
32x-3x-70-104=0
We add all the numbers together, and all the variables
29x-174=0
We move all terms containing x to the left, all other terms to the right
29x=174
x=174/29
x=6
| 1/3y+5=13 | | -9-10m=6-7m+6 | | 16x+26+20x+40=24x-146 | | -8d-9=-6d+9 | | 6.4u-5.1u=3.25 | | (12x)+10x+20=180 | | 3/2a-8=18 | | 2y-5+10y=10y=9 | | 3x+3x+3=3 | | p-5=2p | | 3x3x+3=3 | | 5+10u=9u | | x/3x+1=3x-6/9x-2 | | 2(x-4)+8=4x | | 1=5g-9=7g-6 | | 1-2z=8-9z | | -10v-7=-9v | | F(3)=x^2+2.3x-9 | | 4x-5/3=x+3/2 | | 6x+36=18x-30 | | 3p=10+4p | | 12-9(y+5)=-(1y | | 1-5q=-4q+10 | | -36x+180=0 | | 12(16x–6)=2 | | 9-5r=-6r | | 26-x-3.5=8.5 | | -6+8w=9w | | -w/2.5=8 | | C=0.4x+35 | | a–2=3+6a/3 | | -c/9+6=8 |